The effects of cognitive impairment on the multi-scale dynamics of standing postural control during visual-search in older men - Zhou, Junhong; Manor, Brad; McCarten, John Riley; Wade, Michael G.; Jor’dan, Azizah J. (Frontiers in Aging Neuroscience, 2023)
Background: Cognitive impairment disrupts postural control, particularly when standing while performing an unrelated cognitive task (i.e., dual-tasking). The temporal dynamics of standing postural sway are “complex,” and such complexity may reflect the capacity of the postural control system to adapt to task demands. We aimed to characterize the impact of cognitive impairment on such sway complexity in older adults. Methods: Forty-nine older adult males (Alzheimer’s disease (AD): n=21; mild cognitive impairment (MCI): n=13; cognitively-intact: n=15) completed two 60-second standing trials in each of single-task and visual-search dual-task conditions. In dual-task condition, participants were instructed to count the frequency of a designated letter in a block of letters projected on screen. The sway complexity of center-of-pressure fluctuations in anterior-posterior (AP) and medial-lateral (ML) direction was quantified using multiscale entropy. The dual-task cost to complexity was obtained by calculating the percent change of complexity from single- to dual-task condition. Results: Repeated-measures ANOVAs revealed significant main effects of group (F>4.8, p<0.01) and condition (F=7.7, p<0.007) on both AP and ML sway complexity; and significant interaction between group and condition for ML sway complexity (F=3.7, p=0.03). The AD group had lowest dual-task ML complexity, as well as greater dual-task cost to ML (p=0.03) compared to the other two groups. Visual search task accuracy was correlated with ML sway complexity in the dual-task condition (r=0.42, p=0.007), and the dual-task cost to ML sway complexity (r=0.39, p=0.01) across all participants. Conclusion: AD-related cognitive impairment was associated with a greater relative reduction in postural sway complexity from single- to dual-tasking. Sway complexity appears to be sensitive to the impact of cognitive impairment on standing postural control.